Learning outcomes of Iranian students as educational tourist in Malaysian universities / Maryam Asgari - Asgari, Maryam (2016)
Today, international students are recognized as a rather unique category of tourists. The perceptions of this group are shaped based on whole life experiences in the host country. In response, this thesis develops a model to evaluate the learning outcomes of Iranian students who study in Malaysian universities from the educational tourist perspective. This model extends the effect of service quality, image, price, and student perception on learning outcomes of Iranian students. Learning outcomes is a product of the university that is as an indicator of institutional quality and effectiveness. In addition, this model examines the influence of these constructs on learning outcomes by mediating effect of satisfaction. The methodology of study is based on mixed method research. The researcher used embedding dataset in the mixed method in order to support the proposed theoretical model. In the qualitative part, a semi-structured in-depth interview with Iranian students was conducted in order to gain a deeper understanding of the perception of those respondents towards Malaysian universities and Malaysia as a destination study. In this regard, the constant comparative method was used for data analysis as it allowed the researchers to identify foundation categories by focusing on three different types of coding (open, axial, and selective). In the quantitative part, a survey, by using self-administered questionnaires has been adopted to collect data for the constructs proposed in the theoretical model from Iranian students who are in the last year of their studies, graduated, or have graduated from Malaysia and starting with another degree. Structural equation modeling is also used to validate the model. The results of the study indicate that satisfaction is a complete mediation variable between image and learning outcomes. The results also reveal that satisfaction is a partial mediation variable between price and learning outcomes. Finally, the model failed to support the relationships between service quality, student perception and the learning outcomes of Iranian students, as well as by mediating effect of satisfaction. These results have extensive practical implications for the education and tourism organizations. Managers of universities must pay attention to reliable, responsive, and empathetic services which are indeed related to improved service quality perceptions. A commitment to excellence in the delivery of services causes student satisfaction as international students have different forms of motivation for studying abroad. Lastly, a favorable image can boost a university attraction through increased student satisfaction. Likewise, high international image and prestige of a destination is an attraction to international students as it is expected that image and prestige would open up better career opportunities for them. Finally, this thesis reveals the perceptions of Iranian international students towards Malaysian universities and Malaysia as a destination study.